Two remarkable new species of Glaucocharis (Lepidoptera, Crambidae, Crambinae) from the Ogasawara Islands, Japan - Matsui, Yuki; Hamaguchi, Junpei; Yagi, Sadahisa; Hirowatari, Toshiya (Zootaxa, 2024)
We describe two new species of the genus Glaucocharis from the Ogasawara Islands of Japan: G. triochellaris Matsui, Yagi & Hirowatari, sp. nov. and G. plumbofascialis Matsui, Yagi & Hirowatari, sp. nov. The new species with remarkable morphological characters are easily distinguished from congeneric species. We provide photographs of adult, male and female genitalia. Molecular phylogenetic analysis revealed a sister relationship between the two new species and the monophyly of Glaucocharis.